Adsorption of Bromo Phenol Red Dye from Aqueous Solution by Iraqi Bentonite Clay - Al-Dulaimy, Zainab Abbas Hassan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This studies deals with investigated the potential of a Iraqi bentonite clay for the adsorption of bromo phenol red dye from contaminated water. Impulse adsorption experiments were performed. The contact time influence of initial dye concentration, temperature, pH, ionic strength, partical size adsorbent and adsorbent dosage on bromo phenol red adsorption are investigated in a series of batch adsorption experiments. Adsorption equilibrium data were analyzed and described by the Freundlich, Langmuir and temkin isotherms equations. Thermodynamic parameters inclusive the Gibbs free energy (∆G•), enthalpy (∆H•), and entropy (∆S•), were also calculated. These parameters specified that adsorption of bromo phenol red onto bentonite was functional, more spontaneous and endothermic with increase of temperatures from 298.15 to 313.15 K.